Dawet Ireng Development Model as Purworejo's Distinguished Local Product - Agus Fitri Yanto; Danis Imam Bachtiar (Indonesian Journal Of Business And Economics, 2018)
Ministry of Cooperatives and Small and Medium Enterprises data shows that in 2012, MSMEs absorb 97.16% of all workforce in Indonesia. Even UMKM's contribution to the value of Indonesia's Gross Domestic Product reached 59.08%. While MSMEs in Central Java Province, the biggest supporting sector is trade which in 2011 reached 28,362 units. With 40.38% of total SMEs in Central Java, MSMEs trade proved to provide great support for the dynamics of Central Java and nationally economy, including SMEs in Purworejo District. Purworejo has a variety of local products that have penetrated national and international markets such as VCO, mangosteen peel herbal products and coconut sugar powder. However, various potentials and superior products Purworejo it must be increasingly competing with various modern products. The success of some products Purworejo SMEs apparently can not be followed by other products that actually become icon Purworejo, such as clorot, lompong cake, and dawet ireng. When dawet ireng increasingly widely known in various regions, it is in Purworejo felt to be an ordinary product and far from a distinctive impression. The position of dawet ireng increasingly much different from more modern beverage products and the present. This is apparent from the more demanding of a similar kind of drinks. If this is left then dawet ireng increasingly shifted. Based on this matter, it is necessary to design dawet ireng development model as a unique local product of Purworejo so it is more competitive and really become the regional icon that can be equated with modern beverage products today.